ANALISIS PENGARUH DISIPLIN KERJA DAN KINERJA KARYAWAN - Akhmad Nurrofi (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2016)
Employee performance in a company is needed. This researchconcerning employee performance problem, Samples used by all population are36 respondents with Samleng Census technique data analysis used instrumenttest, multiple regression analysis and hypothesis test.The results of this studyPartial regression coefficient Motivation work (X1) on employee workdiscipline. After analyzed obtained value tcount X1 (3.602)> ttable (2.03), thenHo is rejected and Ha accepted the conclusion of variables Motivation of workhave a positive and significant impact on employee discipline.2. PartialRegression Coefficient of Leadership Style (X2) on Employee Work Discipline.After analyzed, tcount X2 (4,549)> ttable (2.03), hence Ha accepted and Horejected conclusion of Leadership Variable have positive and significantinfluence to employee work discipline.Partial regression coefficient Motivationwork (X1) on employee performance. After analyzed obtained value tcount X1(1.396)> ttable (2.03), then Ho is rejected and Ha accepted the conclusion ofwork motivation variable and has no effect and not significant on employeeperformance.4. Partial Regression Coefficient of Leadership Style (X2) onemployee performance. After analyzed obtained value tcount X2 (3.895)> ttable(2.03), then Ha accepted and Ho rejected conclusion Variable Style Leadershave a positive and significant impact on employee performance.Regressioncoefficient Discipline work (Y1) on Employee Performance. After analyzedobtained tcount Y1 (6,075)> ttable (2.03), hence Ha accepted and Ho rejectedconclusion Variable of work discipline have positive and significant effect toemployee performance.